Performance Audit of Prevention and Control of Diseases Programme in Arunachal Pradesh (1996-2001) - CAG of India (CAG of India, 2002)
The review highlights failure of the State Government to utilise Central assistance of Rs.1.44 crore (National TB Control Programme – Rs. 0.20 crore, National Programme for Control of Blindness – Rs. 0.40 crore and National Aids Control Programme – Rs.0.84 crore), non-implementation of Revised strategy for National Tuberculosis Control Programme (RNTCP), non-establishment of eye bank, unnecessary blockade of fund, shortfall in achievement of targets fixed for different components of these programme and lack of proper monitoring of implementation of these programmes. Main audit findings are summarised below: 1. Against total releases of Rs. 5.03 crore (Rs. 0.27 crore RNTCP, Rs. 0.58 crore NPCB and Rs. 4.18 crore NACP) by the Government of India, Rs. 3.59 crore were utilised during 1996-2001 leaving Rs.1.44 crore (29 percent) unspent. 2. Under RNTCP, none of the 4 DTCs could start functioning due to delay in formation of societies. 3. Under NTCP, in 7 out of 13 districts in the State, no DTCs were established. Even the 6 functional DTCs were not provided with all the essential equipment. 4. Unproductive expenditure of Rs.8.71 lakh due to non-functioning of the State TB Training Demonstration Centre at Naharlagun. 5. Nine districts with a population of 5.45 lakh were deprived of the benefit of district mobile eye units (DMUs) due to non-appointment of eye specialist etc. for 4 districts and non-sanctioning of the DMUs for 5 districts. 6. Shortfall in achievement in cataract surgery during 1996-2001 varied from 35 to 73 per cent. 7. No eye bank was established either in the Government sector nor by NGOs. 8. Unnecessary locking up of fund of Rs.13.00 lakh for purchase of 6500 wall clocks for distribution/display to different hostels/schools prior to selection of NGO. 9. Doubtful expenditure of Rs.7.19 lakh for procurement of consumables, reagents etc.
For the Period 1996-97 to 2000-01